National Board Certification as a Signal of Cooperating Teacher Quality - Dan Goldhaber; John Krieg; Roddy Theobald; Grace Falken (AERA Open)
Prior research suggests that more effective teachers may also be better mentors for preservice student teachers, but the specific measures of cooperating teacher effectiveness considered in the prior quantitative literature (value added and performance evaluations) are infrequently observable to individuals responsible for student teaching placements. In this paper, we consider a more easily observed proxy for mentor effectiveness: National Board (NB) Certification. We find that NB teachers are considerably more likely to host student teachers, and student teachers supervised by NB teachers are slightly more likely to be hired within three years, all else equal, but we find no consistent significant relationship between cooperating teacher NB Certification and the later attrition or value added of the teachers they supervised.